Early childhood education learning revolution: the role of technology-based interactive methods in enhancing teacher creativity - Zebar, A.; Sembiring, Putri Sari Ulfa; Harahap, Baginda; Habib, Muhammad Ranu Al (Cendikia : Media Jurnal Ilmiah Pendidikan, 2025)
The rapid advancement of technology has transformed the landscape of early childhood education (ECE), urging educators to adopt innovative approaches in teaching. This study investigates the role of technology-based interactive methods in enhancing the creativity of ECE teachers. The sample size ranges from 30 to 50 ECE teachers, selected based on specific criteria such as teaching experience and the use of technology in the classroom. Using a quantitative descriptive-correlational method, data were collected through questionnaires from actively teaching ECE educators in Medan who utilize digital tools in the classroom. Multiple linear regression analysis revealed that components such as digital learning applications, interactive content development, technology-supported instructional design, and teacher-student digital engagement have a significant and positive effect on teacher creativity. The model demonstrated strong explanatory power, with an R² value of 67.2%. These findings highlight the potential of technology to not only enrich children's learning experiences but also to support teachers in developing more creative, engaging, and relevant teaching strategies. This research underlines the importance of digital literacy and training programs for ECE educators in the digital age.